Ritual as a classical social technology of China (philosophical and sociological analysis) - M. Yu. Zakharov (Вестник университета, 2019)
The nature of Chinese ritual and features of its use in the social sphere of society have been examined. The potential of ritual as a social technology has been revealed. The modern scientifi understanding of the ritual has been analyzed, the content of the internal and external aspects has been studied, their interconnection and interdependence have been shown, an attempt has been made to understand the role of the ritual in traditional culture. The conclusion has been made about the social significance of the ritual, its place in the complex mechanism of self-preservation and reproduction of social behavior, the socially significant function fulfilment of the stable life, traditional regulator in modern China.